2021
DOI: 10.1080/20002297.2021.1983322
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and antibiotic-resistance of different Staphylococcus species identified by matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) isolated from the oral cavity

Abstract: Background: The use of antibiotics in dentistry is associated with the emergence and spread of antibiotic-resistant microorganisms, including commensal staphylococci. Methods: A total of 367 oral samples were collected, from which staphylococci were isolated and identified by using matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF). The antibiotic susceptibility of the isolates was determined and molecular characteristics for methicillin-resistant staphylococci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Our Polish Reference Center for Staphylococci is a leading center for bacteriophage typing of S. aureus strains involved in various infections, with considerable achievements in this field [ 12 , 13 , 14 , 15 , 16 ]. Recently, the oral cavity has gained attention as a reservoir of antibiotic-resistant S. aureus strains and a source of their spread to other anatomical regions [ 17 , 18 , 19 ]. However, the knowledge of the sensitivity of oral S. aureus to bacteriophages and the potential therapeutic application of the latter are fairly limited.…”
Section: Introductionmentioning
confidence: 99%
“…Our Polish Reference Center for Staphylococci is a leading center for bacteriophage typing of S. aureus strains involved in various infections, with considerable achievements in this field [ 12 , 13 , 14 , 15 , 16 ]. Recently, the oral cavity has gained attention as a reservoir of antibiotic-resistant S. aureus strains and a source of their spread to other anatomical regions [ 17 , 18 , 19 ]. However, the knowledge of the sensitivity of oral S. aureus to bacteriophages and the potential therapeutic application of the latter are fairly limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inappropriate use of antimicrobials in oral cavity is still performed in dentistry ( Holmes et al, 2016 ; Gross et al, 2021 ). Recent studies showed that the oral cavity is considered one of major reservoirs of antimicrobial resistance genes in human body ( Kearney et al, 2020 ; Garbacz et al, 2021 ). In the present study we showed that HEF and PA have a narrow-spectrum therapeutic effect against P. gingivalis , which is recognized as a keystone pathobiont for development of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous studies had identified antibiotic-resistant bacteria in dental offices: S. maltophilia resistant to trimethoprim were found in an air sample of a dental waiting room [ 10 ], and S. aureus resistant to methicillin were found on the surfaces of dental consulting rooms [ 4 , 8 , 9 ]. Several Staphylococcus species resistant to antibiotics (mainly resistant to penicillin, gentamicin and erythromycin) were isolated from the oral cavity: mainly S. aureus , but also numerous coagulase-negative staphylococci including S. haemolyticus [ 25 ]. Therefore, the oral cavity should be considered to be a potential reservoir and source of antibiotic-resistant bacteria spread in the environment.…”
Section: Discussionmentioning
confidence: 99%